2019
DOI: 10.31635/ccschem.019.20190008
|View full text |Cite
|
Sign up to set email alerts
|

Cu 2 O-Supported Atomically Dispersed Pd Catalysts for Semihydrogenation of Terminal Alkynes: Critical Role of Oxide Supports

Abstract: Atomically dispersed catalysts have demonstrated superior catalytic performance in many chemical transformations. However, limited success has been achieved in applying oxide-supported atomically dispersed catalysts to semihydrogenation of alkynes under mild conditions. By utilizing various metal oxides (e.g., Cu2O, Al2O3, ZnO, and TiO2) as supports for atomically dispersed Pd catalysts, we demonstrate herein the critical role of the oxidation state and coordinate environment of Pd centers in their catalytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…The catalytic activity of Pd 2 CO/TiO 2 in the hydrogenation of styrene was evaluated and compared with those of single-atom Pd catalysts, such as Pd 1 /TiO 2 -EG (denoted as Pd 1 ) with single-atom Pd on ethylene glycolate-stabilized TiO 2 (B) [43], and Pd 1 /TiO 2 -cal (denoted as Pd 1 -cal) with surface ethylene glycolate removed by calcination [44]. As shown in Figure 3(c), Pd 2 CO/TiO 2 exhibited a much higher activity than the two single-atom Pd catalysts [45,46]. The calculated TOFs based on the surface Pd atoms ( Figure S27) revealed that, with the presence of CO binding, the supported Pd 2 clusters were indeed as active as the surface Pd on large NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic activity of Pd 2 CO/TiO 2 in the hydrogenation of styrene was evaluated and compared with those of single-atom Pd catalysts, such as Pd 1 /TiO 2 -EG (denoted as Pd 1 ) with single-atom Pd on ethylene glycolate-stabilized TiO 2 (B) [43], and Pd 1 /TiO 2 -cal (denoted as Pd 1 -cal) with surface ethylene glycolate removed by calcination [44]. As shown in Figure 3(c), Pd 2 CO/TiO 2 exhibited a much higher activity than the two single-atom Pd catalysts [45,46]. The calculated TOFs based on the surface Pd atoms ( Figure S27) revealed that, with the presence of CO binding, the supported Pd 2 clusters were indeed as active as the surface Pd on large NPs.…”
Section: Resultsmentioning
confidence: 99%
“…These notwithstanding, peaks revealed by deconvolution at 934.5, 940.5 and 943.6 eV were assigned to Cu(II), indicating the main content to be of CuO. 26,[44][45][46][47] Lastly, the high-resolution spectrum of Ag 3d exhibited peaks at 374.4 eV and 368.4 eV (Fig. 3b), which could be attributed to Ag 3d 5/2 and Ag 3d 3/2 in Ag(0).…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 95%
“…25 Moreover, similar effects where Cu surfaces have partly oxidized have been reported, Cu 2 O/CuO has hosted NPs such as Pd, Ni, and Ag and the resulting composites have displayed remarkable catalytic activity. [26][27][28][29] With its indirect narrow band gap (1.3-1.51 eV), 30 the CuO has been argued to act as a semiconductor, possessing a strong absorption in the visible region, high carrier concentration and low toxicity. As a visible light-activated photocatalyst, CuO has already exhibited excellent performance in the degradation of organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…The as-prepared Pt SA/TiO2 exhibited enhanced anti-Markovnikov alkene hydrosilylation and photocatalytic hydrogen generation properties. Similarly, many metal oxide-based SACs were synthesized by the co-precipitation or electrostatic adsorption, such as Rh SA/TiO2 [76], Pt SA/Fe2O3 [77], Pt SA/WO3−x [78], Pt SA/CeO2 [79,80], Pd SA/CeO2 [81], Pd SA/Cu2O [82], Au SA/CuO [83], Pt SA/ZrO2 [84] and Pt SA/Ni(OH)x [85] (Fig. 3(c)) reported by many research groups in SACs.…”
Section: Sacs Supported On Metal Oxidesmentioning
confidence: 99%